KEBIJAKAN PENCAPAIAN SWASEMBADA DAGING SAPI TAHUN 2014 - Edmira Rivani; Rafika Sari (Jurnal Ekonomi & Kebijakan Publik, 2010)
The ministry of Agriculture has launched the Strategic Plan (Renstra) in 2010‐2014 to achieve food self‐sufficiency. One of the targets aims to increase the beef production to reach 550 thousand tonnes by 2014. It will be done to continue the availability of beef. However, its efforts to achieve the goal of beef self‐sufficiency must be supported by increased the number of livestocks. This paper discussed the policy of beef self‐sufficiency and the solution how to reach the self‐sufficiency based on the 2010’ Renstra.